Skötsel av älgskadade bestånd - Skoog, Johan (2005)
Sweden has today the highest moose (Alces alces) population in the world. The population has been very high since the late seventies and in the beginning of the eighties there was a big "moose explosion". The main food source for moose during the winter is young pine (Pinus sylvestris) and birch (Betula spp.). The high moose population has therefore lead to high damage on pine forests over big areas. These forests are now about to be commercial thinned for the first time. Because of that the difficult, but important question of how to manage these damaged forests in the best way arises. The aim of this work was to investigate if there were some alternative management programs for the damaged forests which were better than those used today. Therefore the following three questions were formulated: - Is it profitable to take away all the damaged stems at the first commercial thinning, to be able to manage an undamaged "repaired" stand? - Should you clear cut the stands with the most severe damage earlier than normal and instead regenerate with spruce (Picea abies) if the site index is good? - Is it profitable to cross-cut damaged stands differently? This exam work was done as an assignment to Bergvik Skog. It was performed as an inventory and a following calculation of the material, but it was also done as a literature study. The inventory took place at the "Nornområdet" in Bergslagen where there already is a moose project going on. Twenty-three randomly chosen pine stands with a height around 10 meters were inventoried. The invented data included both forest data and data of the moose damage. The result showed that most stands had serious damage, in average 46.9 % of the pine had viewable damage. A simulation of eight different management alternatives was done for each stand. These were conducted with ProdMod2, which is a computer program that can calculate the production on a stand. For the economic calculations there was constructed a program in Excel in which net values and net present values could be ...